Actividades recreativas para prevenir la obesidad en adolescentes de 10mo año paralelo A de la Unidad Educativa Fernando Suarez Palacio, Loja 2024. - Ramos Liviapoma, Edwin José (2024)
Obesity in teenagers is a public health problem of growing concern worldwide. This condition is characterized by excess body fat that can have serious consequences for both the physical health and emotional well-being of young people. Recreational activities are presented as an alternative to prevent obesity in teenagers. In this regard, the objective of the research is focused on developing recreational activities to prevent obesity in teenagers from the 10th-grade class A of the Fernando Suárez Palacio Educational Unit." The present study is descriptive and correlational, with a mixed qualitative and quantitative approach; its design is quasi-experimental and is based on inductive, deductive, analytical-synthetic and statistical methods. The results are obtained through the application of the Body Mass Index (BMI) pre-test and post-test, the Ruffier-Dickson resistance test and a student survey. The data evidenced in the analysis of the results with the instruments used show that the implementation of a didactic proposal of recreational activities contributed to the prevention of obesity. These activities not only encourage students' active participation in physical exercise, but also promote healthy lifestyle habits; thus concluding that recreational activities play a positive role in the prevention of obesity in teenagers, as they prepare students to adopt a healthy and efficient lifestyle by practicing some physical activity or sport, which is reflected in improved physical well-being. Key words: recreational activities, obesity, teenagers, body mass index, endurance.